The Carbon Stock Environment of Mapping Vegetation in UMMAT Education Forest West Rinjani - Fatuh Rahman; Sukuryadi; Nurudin; Harry Irawan Johari (Postgraduate, University of Mataram, 2023)
Indonesia is a country that has a role as carbon sink which is very influential on climate change in the Southeast Asian region, on the island of Lombok there are clusters that stretch forest hills from West Rinjani to East Rinjani. This Forest Protected or Educational Forest which has been controlled has an area of ​​more than 90 hectares with based on Minister Environment and forest Republic Indonesia SK 405/MENLHK/Setjen/PLA.0/6/2016 in couple years ago are diversity of flora and several types of plants and trees. Land fires or forest areas in Mount Rinjani National Park on the eve of the 78th Indonesian independence along the Aik Berik hiking trail were caused by humans or due to negligence. The community thinks about the condition, the destruction as well as the benefits of Protected Forest/Edu Forest, residents have perceptions about carbon storage and the benefits of Protected forest as a carbon store as well as people’s perceptions about climate change that is happening. The Data was obtained systematically have marked 9 plots divers growth stage 20x20 m for tree shape, 10x10m for poles, 5x5m for saplings, 2x2m for seedlings, 1x1m for wet grass. The form of balance and harmony that is still protected by Muslims the bond between human and Allah, and their environment. The Universe of God’s gave gift to manage and maintain it, so that it remains sustainable and good. In the Al-Qur’an it is explicitly stated that all forms of damage that exist on this earth are the result of human activities in interacting with their environment. That the universe was created by Allah as a form of His love for humans. Allah created and this nature for the benefit of humans. Nature is made a verse or a sign of the existence and omnipotence of Allah. Realizing that the universe is God’s creation, then taking care of the earth and preserving it is part of the consequences of this monotheistic belief. The primary data used is hill mapping, settlements and watershed observations of perceptions about carbon storage to vegetation, while the purpose of the activity or research is to carry out an analysis of identifying community perceptions of carbon storage and forest vegetation in Batu Bolong Village.